Provision of an emergency theatre in tertiary hospitals is cost-effective : audit and cost of cancelled planned elective general surgical operations at Pietersburg Hospital, Limpopo Province, South Africa - Bhuiyan, M. M. Z. U.; Mavhungu, R.; Machowski, A. (South African Medical Journal, 2017)
Background. Cancellations of planned elective surgical operations increase financial cost to the patient and the hospital. Objectives. To determine the rate and reasons for cancellations, estimate the cost incurred by such cancellations and recommend possible solutions. Methods. We did a prospective descriptive study of cancellations of elective general surgical operations over the 1-year period January - December 2014 in the main theatre at Pietersburg (PTB) Hospital, Limpopo Province, South Africa. All patients listed on the theatre booking slate for elective general surgical operations before the cut-off time of 13h00 on the day before the anticipated operation were included. Epi Info version 7 was used to analyse the data and derive the descriptive statistics. Results. There were 537 booked patients (median age 47 years, range 1 - 94); a total of 298 operations were performed, and 239 were cancelled (cancellation rate 44.5%). Reasons for cancellation were as follows: theatre needed for an emergency n=154 (64.4%), theatre equipment failure and lack of consumables n=17 (7.1%), non-theatre equipment failure n=10 (4.2%), prolonged time of operations n=13 (5.4%), abnormal blood results n=8 (3.3%), patient comorbidity and poor general condition n=9 (3.8%), patients absent from the ward n=8 (3.3%), patients not starved n=2 (0.8%), patients’ condition improved significantly n=3 (1.3%), nurses’ strike n=5 (2.1%), rebooking of cases for senior surgeons or other specialty n=2 (0.8%), and other reasons n=8 (3.3%). The cost per inpatient per day was estimated at ZAR4 890 at PTB Hospital and ZAR2 100 at district hospitals, and the total cost per cancelled operation was ZAR25 860. Conclusions. Over the 1-year period 44.5% of elective operations at PTB Hospital were cancelled, 64.4% because the theatre was needed for an emergency operation. We recommend that a theatre dedicated to emergencies be opened at PTB Hospital. The cost incurred due to cancellations was about ZAR6 million for the hospital, with additional cost and emotional trauma for the patients.
Journal article published in the South African Medical Journal 2017;107(3):239-242. DOI:10.7196/SAMJ.2017.v107i3.10687
Keywords: Surgical operations; Emergency theatre; Operations, Surgical